Haiti : Staff Report for the 2000 Article IV Consultation and for a Staff-Monitored Program (SMP) for FY 2000/01. (IMF Staff Country Reports; Country Report ;, 2001)
Haiti's economic performance deteriorated as a result of continuing political crisis. The ongoing political crisis has impeded the implementation of a comprehensive, donor-backed effort to remove Haiti's serious structural impediments. The economic program seeks to help the government reestablish macroeconomic stability during the political transition, alleviate pressure on the exchange rate, and restore inflation to a downward path. Credit policy should continue to be restrained through open market operations. The IMF staff commends the measures taken to improve the supervision and health of the banking system.